Snail Diversity across Maharashtra Habitats: Comprehensive Review (International Journal of Scientific Research in Science and Technology, 2026)
Mollusca, the second-largest invertebrate phylum, encompasses Gastropoda (snails/slugs), Bivalvia, and Cephalopoda. Gastropods—soft-bodied organisms with calcified shells—dominate Maharashtra’s malacofauna. This comprehensive literature review synthesizes 40+ studies documenting terrestrial and aquatic gastropod diversity across Maharashtra’s districts, cataloging 142 species (48 genera, 23 families), new records, seasonal variations, species richness, relative abundance, and population dynamics. Raigad exhibits highest diversity (63 species), followed by Pune (49), Nashik (42), and Amravati (30+). Urbanization, pollution, and invasives (Achatina fulica) threaten native fauna. Traditional morphological identification limits cryptic species detection; DNA barcoding is recommended for comprehensive documentation. Findings establish baseline malacofauna knowledge, identify research hotspots / gaps, and inform conservation strategies. The review underscores ecological roles (bioindicators, nutrient cycling) and highlights urgent need for systematic molecular surveys to preserve Maharashtra’s gastropod heritage amid anthropogenic pressures.